Optimal Timing of Administration of Direct-acting Antivirals for Patients With Hepatitis C-associated Hepatocellular Carcinoma Undergoing Liver Transplantation. Issue 4 (October 2021) - Turgeon, Michael K.; Shah, Shimul A.; Delman, Aaron M.; Tran, Benjamin V.; Agopian, Vatche G.; Wedd, Joel P.; Magliocca, Joseph F.; Kim, Ahyoung; Cameron, Andrew; Olyaei, Ali; Orloff, Susan L.; Anderson, Matthew P.; et al.
Abstract : Objective: To investigate the optimal timing of direct acting antiviral (DAA) administration in patients with hepatitis C-associated hepatocellular carcinoma (HCC) undergoing liver transplantation (LT). Summary of Background Data: In patients with hepatitis C (HCV) associated HCC undergoing LT, the optimal timing of direct-acting antivirals (DAA) administration to achieve sustained virologic response (SVR) and improved oncologic outcomes remains a topic of much debate. Methods: The United States HCC LT Consortium (2015–2019) was reviewed for patients with primary HCV-associated HCC who underwent LT and received DAA therapy at 20 institutions. Primary outcomes were SVR and HCC recurrence-free survival (RFS). Results: Of 857 patients, 725 were within Milan criteria. SVR was associated with improved 5-year RFS (92% vs 77%, P < 0.01). Patients who received DAAs pre-LT, 0–3 months post-LT, and ≥3 months post-LT had SVR rates of 91%, 92%, and 82%, and 5-year RFS of 93%, 94%, and 87%, respectively. Among 427 HCV treatment-naïve patients (no previous interferon therapy), patients who achieved SVR with DAAs had improved 5-year RFS (93% vs 76%, P < 0.01). Patients who received DAAs pre-LT, 0–3 months post-LT, and ≥3 months post-LT had SVR rates of 91%, 93%, and 78% ( P < 0.01) and 5-year RFS of 93%, 100%, and 83% ( P = 0.01). Conclusions: The optimal timing of DAA therapy appears to be 0 to 3 months after LT for HCV-associated HCC, given increased rates of SVR and improved RFS. Delayed administration after transplant should be avoided. A prospective randomized controlled trial is warranted to validate these results.